Pengembangan Sistem Informasi Akuntansi Pengelolaan Kas Desa berbasis Web - Danang Afifuddin Nuryamin; Darya Setia Nugraha; Sugih Sutrisno Putra (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
The Government of Cigugur Girang Village, Parongpong Subdistrict, West Bandung Regency is a government agency at the village level that uses an accounting information system provided by the central government and also uses a manual system. Expenditures and cash receipts transactions conducted in Cigugur Girang Village, Parongpong District, West Bandung Regency are classified as frequent. The system currently in use has not been able to describe expenditure trends and the amount of expenditure for each activity. Because every transaction recorded is still manually resulting in the making of the reports needed by the agency takes longer. As a solution to these problems, the authors designed an application program for spending and cash receipts that are tailored to the circumstances and needs of the agency. The author uses the SDLC and RAD method in designing this application program. Data collection is done by interviewing, observing, and analyzing documents. After the analysis is carried out, the authors designed the application program using Adobe XD. With the design of this protorype program, it is expected to be an alternative used in the accounting information system for expenditure and cash receipts in Cigugur Girang Village, Parongpong District, West Bandung Regency